Forage yield in three pearl millet genotypes submitted to different chicken manure rates - Balbinot Junior, Alvadi Antonio; Hanisch, Ana Lúcia; Vogt, Gilcimar Adriano (Revista de Ciências Agroveterinárias, 2012)
The objectives of this work were to evaluate the forage yield of three pearl millet genotypes under different chicken manure rates and to verify the residual effect of this organic fertilizer on soil. An experiment was carried out in Papanduva, Santa Catarina, Brazil, during the 2008/09 and 2009/10 crop seasons. In the first crop season, three pearl millet genotypes were evaluated: a common genotype and two improved genotype (ADR 500 and LAB 733), which were cultivated under four chicken manure rates (0, 4, 8 and 12 t ha-1). In succession, the multicropping (black oat + common vetch) and pearl millet were cultivated to evaluated the residual effect of this organic fertilizer. The experimental design was a randomized blocks, with four replications. The pearl millet production was evaluated by cuts, while in multicropping between black oat + common vetch was evaluated the total dry mass. There was interaction between pearl millet genotypes and manure rates in relation to total shoot dry mass. The improved genotypes showed the higher performance due to increase manure rate. There was residual effect of this organic fertilizer on the multicroping of black oat + common vetch and pearl millet.